2005
DOI: 10.1111/j.1748-0361.2005.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of HIV Testing and Intention to Test Among Hispanic Farmworkers in South Florida

Abstract: Our findings highlight the importance of routinely offering HIV testing to sexually active individuals in high HIV prevalence areas. They also suggest the need to make testing more accessible to migrant and seasonal farmworkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 24 publications
7
63
1
Order By: Relevance
“…Age and educational level were also significant socioeconomic factors of HIV testing, similarly to other studies (Fernández et al, 2005;Haile et al, 2007). Higher education has been positively associated with HIV knowledge, awareness of availability of health services and HIV testing (Burns et al, 2005;Dias et al, 2004;Stolte et al, 2003;Wong et al, 2004).…”
Section: Wwwintechopencomsupporting
confidence: 66%
“…Age and educational level were also significant socioeconomic factors of HIV testing, similarly to other studies (Fernández et al, 2005;Haile et al, 2007). Higher education has been positively associated with HIV knowledge, awareness of availability of health services and HIV testing (Burns et al, 2005;Dias et al, 2004;Stolte et al, 2003;Wong et al, 2004).…”
Section: Wwwintechopencomsupporting
confidence: 66%
“…44,47 The gender differences may be related to women having more frequent health care encounters, including family planning or antenatal care visits, that offer HIV screening. 52 Late diagnosis was more common among non-Hispanic blacks, Hispanics, and those in the ''other'' race/ethnic group in urban but not in rural areas. Other population-based studies conducted during the last 10 years, found Hispanic ethnicity to be associated with late diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…41,42,[53][54][55][56][57][58][59] Having an undocumented immigration status was associated with not ever being tested for HIV in a study in South Flordia. 52 Reasons identified in other studies for foreign birth being associated with delayed diagnosis include stigma, 56,60,61 language barriers, 58,61 and less knowledge about HIV. 56,61 Late HIV/AIDS diagnosis in urban areas was associated with heterosexual compared with MSM and IDU modes of HIV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Perez et al [58] suggested that women with less education also have less knowledge about and access to prenatal healthcare. Conversely, it has also been found that lower education sometimes leads to higher rates of test acceptance [87,88] .…”
Section: Marital Status: Fabiani Et Almentioning
confidence: 99%